Identification of robust strain designs via tandem pFBA/LMOMA phenotype prediction - Maia, Paulo (2017)
The past two decades have witnessed great advances in the computational modeling and systems biology fields. Soon after the first models of metabolism were developed, methods for phenotype prediction were put forward, as well as strain optimization methods, within the field of Metabolic Engineering. Evolutionary computation has been on the front line, with the proposal of bilevel metaheuristics, where EC works over phenotype simulation, selecting the most promising solutions for bioengineering tasks. Recently, Schuetz and co-workers proposed that the metabolism of bacteria operates close to the Pareto-optimal surface of a three-dimensional space defined by competing objectives. Albeit multi-objective strain optimization approaches focused on bioengineering objectives have been proposed, none tackles the multiobjective nature of the cellular objectives. In this work, we propose multi-objective evolutionary algorithms for strain optimization, where objective functions are defined based on distinct phenotype prediction methods, showing that those can lead to more robust designs, allowing to find solutions in more complex scenarios.